1964
DOI: 10.1017/s0021859600063115
|View full text |Cite
|
Sign up to set email alerts
|

The growth and development of the beef qualities of Angoni cattle (East African shorthorn zebu). Part II. Linear growth and carcass characters

Abstract: Part I described the growth of Angoni cattle as shown by changes in live weight. This Part deals with proportional growth as shown by linear growth and carcass characters.LINEAR GROWTHA virtually complete summary of the basic work on linear growth has been given by Brody (1945) and specific references will therefore be quoted only as required for discussion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Classic studies on domestic species have demonstrated that growth follows a centripetal pattern caused by waves of high growth intensity commencing in distal parts of body extremities and converging along the back line towards the pelvic region (Hammond 1932, Hammond 1940, McMeekan 1940, Walker 1964). This pattern is described as a change in timing of differentially declining growth rates of specific parts of the body (Wallace 1948), which explain the progress of the proximodistal-distoproximal pattern in the limbs, and craniocaudal-cranionasal pattern in the axial skeleton (Hammond 1940, McMeekan 1940, Davies et al 1984.…”
Section: Introductionmentioning
confidence: 99%
“…Classic studies on domestic species have demonstrated that growth follows a centripetal pattern caused by waves of high growth intensity commencing in distal parts of body extremities and converging along the back line towards the pelvic region (Hammond 1932, Hammond 1940, McMeekan 1940, Walker 1964). This pattern is described as a change in timing of differentially declining growth rates of specific parts of the body (Wallace 1948), which explain the progress of the proximodistal-distoproximal pattern in the limbs, and craniocaudal-cranionasal pattern in the axial skeleton (Hammond 1940, McMeekan 1940, Davies et al 1984.…”
Section: Introductionmentioning
confidence: 99%